2021
DOI: 10.1039/d1cp00670c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituting non-polar chains with polar chains on the structural dynamics of small organic molecule and polymer semiconductors

Abstract: The processability and optoelectronic properties of organic semiconductors can be tuned and manipulated via chemical design. The substitution of the popular alkyl side chains by oligoethers has recently been successful...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…194,195 We envision potential directions for this work also to include investigations into polar motifs with more structural similarity to the simple alkyl chain than, for example, oligoethylene glycol chains, which show a preference for the gauche conformation resulting in significantly different structural organization. 155,156 Alkyl chains with terminal hydroxy groups represent one example, explored previously on a polythiophene scaffold with good mixed ionic and electronic conduction behavior despite a very low degree of swelling in aqueous electrolyte as compared to glycolated analogues. 154 Polar motifs that can help guide the structural organization, for instance, through intermolecular hydrogen bonding as known from self-healing organic semiconductors, 196 is another avenue that invites further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…194,195 We envision potential directions for this work also to include investigations into polar motifs with more structural similarity to the simple alkyl chain than, for example, oligoethylene glycol chains, which show a preference for the gauche conformation resulting in significantly different structural organization. 155,156 Alkyl chains with terminal hydroxy groups represent one example, explored previously on a polythiophene scaffold with good mixed ionic and electronic conduction behavior despite a very low degree of swelling in aqueous electrolyte as compared to glycolated analogues. 154 Polar motifs that can help guide the structural organization, for instance, through intermolecular hydrogen bonding as known from self-healing organic semiconductors, 196 is another avenue that invites further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing again dH-PTTP and TEG-PTTP, Guilbert et al investigated in detail the impact of polar chains on structural properties as well as structural dynamics. 156 From single-crystal X-ray diffraction analysis (Figure 4c), the thiophene−thiophene dihedral angle is in both compounds found to be 180°(s-trans conformation) as expected with both compounds displaying a herringbone packing structure. However, the thiophene−phenylene dihedral angle is significantly larger for TEG-PTTP (17.3°vs 3.8°for dH-PTTP), most likely related to the markedly different chain conformations observed for the two compounds.…”
Section: Aqueous and Nonspecific Ionic Interactionsmentioning
confidence: 99%
“…For instance, long linear alkyl chains yield a broad liquid crystalline phase at low temperatures. Introduction of heteroatoms in the aliphatic chains results in a decrease of the melting temperature [20]. The core planarity of nonbenzofused systems can be improved by weak intramolecular S⋯O 4 coupling between an alkoxy group and a sulfur-containing heterocycle such as thiophene leading to a solid-state "conformational lock" [21].…”
Section: Introductionmentioning
confidence: 99%
“…Neutron spectroscopy offers master tools for probing the structural dynamics of organic semiconductors. Although it is still an under-used method in this field, recent studies have demonstrated its power in the framework of (i) OSCs, ,,, (ii) charge transport, and (iii) photochemical water splitting materials. Neutron spectroscopy encompasses techniques covering synergistically different time scales at the nanometer length scale. It can be used to gain deeper and newer insights into the structure–dynamics–properties relationship.…”
Section: Introductionmentioning
confidence: 99%